The efficacy of the 11 and the 11+ in injury prevention and physical fitness improvement on male collegiate football teams. Issue 4 (27th March 2011) - Saho, Y; Suzuki, T; Setojima, M; Ogai, T; Fukubayashi, T
Abstract : Background: The 11 and The 11+ are accepted effective injury-prevention training programs for junior football players. However, their impact on physical fitness is unclear. Objective: To elucidate the effectiveness of The 11 and The 11+A in injury prevention and physical fitness improvement. Design: A prospective and pre-post intervention study. Setting: The first division of a Japanese collegiate football league. Participants: This study included 182 collegiate male football players, who were divided into three groups: The 11 (n=62), The 11+A (n=60) and Control (n=59). 77 players were evaluated for physical fitness. Interventions: The 11 program, originally developed by FIFA, and The 11+A, by one of the authors, were conducted once or twice a week for 6 months. The 11+A focuses on plyometric training and differs slightly from The 11+. Main outcome measures: Injury incidence rates during football (game and training), game and training were reported as the number of injuries per 1000 player-hours (PH). Using several field tests (sprint, pro-agility, bounding and balance), each subject's physical fitness level was evaluated prior to and 6 months after training. Results: The incidence rates during football, game and training were 3.62, 19.18 and 2.58 injuries/PH in the Control group, 2.27, 11.92 and 1.53 injuries/PH in The 11 group and 2.24, 10.75 and 1.75 injuries/PH in The 11+A group, respectively. The injury incidence rate during football was significantly lower in both the training groups than in the Control group (p<0.05). Pro-agility time was significantly decreased in both training groups than in the Control groups (p<0.05). Balance ability improved significantly only in the 11 group (p<0.05). Conclusion: The 11 and The 11+A were effective in injury prevention and physical fitness improvement.